In vitro ferredoxin-dependent desaturation of fatty acids in cyanobacterial thylakoid membranes. - Wada, H (1993)
Thylakoid membranes isolated from the cyanobacterium Synechocystis sp. strain PCC6803 were capable of desaturating the acyl groups in monogalactosyl diacylglycerol. This desaturation reaction required the reduced form of ferredoxin.